A quantitative analysis of the magnitude of money laundering activities and its determinants in the United Arab Emirates - Ghuloom, Aljasmi Maryam Abbas Mohammad (Tanjong Malim, 2024)
A quantitative analysis of the magnitude of money laundering activities and its determinants in the United Arab Emirates by Ghuloom, Aljasmi Maryam Abbas Mohammad